A synthetic curcumin-like diarylpentanoid analog inhibits rhinovirus infection in H1 hela cells via multiple antiviral mechanisms - Liew, Kong Yen; Chee, Hui-Yee; Abas, Faridah; Leong, Sze Wei; Harith, Hanis Hazeera; Ahmad Israf, Daud; Sulaiman, Mohd Roslan; Tham, Chau Ling (Springer, 2024)
Background: Rhinovirus (RV) infection is a major cause of common colds and asthma exacerbations, with no antiviral drug available. Curcumin exhibits broad-spectrum antiviral activities, but its therapeutic effect is limited by a poor pharmacokinetics profile. Curcumin-like diarylpentanoid analogs, particularly 2-benzoyl-6-(3,4-dihydroxybenzylidene)cyclohexen-1-ol (BDHBC) and 5-(3,4-dihydroxyphenyl)-3-hydroxy-1-(2-hydroxyphenyl)penta-2,4-dien-1-one (DHHPD), have better solubility and stability compared to curcumin. Objectives: Therefore, this study aims to evaluate and compare the antiviral effects of curcumin, BDHBC, and DHHPD in an in vitro model of RV infection. Methods: The inhibitory effects on RV-16 infection in H1 HeLa cells were assessed using cytopathic effect (CPE) reduction assay, virus yield reduction assay, RT-qPCR, and Western blot. Antiviral effects in different modes of treatment (pre-, co-, and post-treatment) were also compared. Additionally, intercellular adhesion molecule 1 (ICAM-1) expression, RV binding, and infectivity were measured with Western blot, flow cytometry, and virucidal assay, respectively. Results: When used as a post-treatment, BDHBC (EC50: 4.19 µM; SI: 8.32) demonstrated stronger antiviral potential on RV-16 compared to DHHPD (EC50: 18.24 µM; SI: 1.82) and curcumin (less than 50% inhibition). BDHBC also showed the strongest inhibitory effect on RV-induced CPE, virus yield, vRNA, and viral proteins (P1, VP0, and VP2). Furthermore, BDHBC pre-treatment has a prophylactic effect against RV infection, which was attributed to reduced basal expression of ICAM-1. However, it did not affect virus binding, but exerted virucidal activity on RV-16, contributing to its antiviral effect during co-treatment. Conclusion: BDHBC exhibits multiple antiviral mechanisms against RV infection and thus could be a potential antiviral agent for RV. Graphical Abstract: (Figure presented.)